Music therapy and radiation oncology: State of art and future directions. (May 2020) - Nardone, Valerio; Vinciguerra, Claudia; Correale, Pierpaolo; Guida, Cesare; Tini, Paolo; Reginelli, Alfonso; Cappabianca, Salvatore
Abstract: Background: Effectiveness of music-based interventions (Music therapy, MT) on cancer patients' is a current research theme. Oncology patients may respond to radiation treatment (RT) with anxiety expressed as stress, fear, depression, and frustration. Objectives: The aim of this review is to discuss the effectiveness of MT in patients undergoing RT. Data sources: All English medical papers registered in the Web of Knowledge, PubMed, Google Scholar and ScienceDirect from March 1999 to March 2019. Inclusion and exclusion criteria: We selected all the articles concerning the use of MT in pre-RT anxiety and distress during RT treatment. Results: Out of 1184 articles selected, 132 abstracts were analyzed and 13 papers were finally evaluated for the current analysis, for a total of 946 participants. Discussion: We investigated the role and the efficacy of MT for patients receiving RT and the future challenges in the clinical management of oncology patients before and during radiotherapy. Highlights: Effectiveness of music therapy on mood disorders, quality of life and pain in cancer patients is a current research theme. We have performed a systematic review in literature in oncology patients undergoing RT. All the studies were single site, the outcome measures were inconsistent and the randomization procedure was often unclear. In the next future, it would be essential to define standardized protocols and multicenter strategies to investigate this topic.